Learning to earn? The role of performance grades in higher education. Issue 9 (2nd September 2017) - Lynch, Raymond; Hennessy, Jennifer
Abstract : Through the reinforcement of shared assessment biographies, the provision of performance grades has been socially constructed as an operating imperative within the assessment practices of universities. The drive towards enhanced accountability through the production of quantifiable outcomes has also played a naturalising role in this practice. In so doing, it has ostensibly removed the need for debate surrounding grading practices in general and diverted focus to issues concerning the reliability and validity of assessment instruments and the resulting grades awarded. This article aims to examine the ubiquitous provision of performance grades from both a pedagogical and ideological perspective. It explores the current espoused function of letter and numeric grades within higher education against contemporary educational research and questions the relationship between performance grades and the broader, liberal educational goals of universities. Finally, the paper highlights alternative models and concludes by raising questions regarding the wider social value of university education.